2014
DOI: 10.1002/ana.24145
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine exacerbates β‐amyloid pathology, tau pathology, and cognitive deficit in a mouse model of Alzheimer disease with plaques and tangles

Abstract: Objective High level of homocysteine (Hcy) is a recognized risk factor for developing Alzheimer disease (AD). However, the mechanisms involved are unknown. Previously, it was shown that high Hcy increases brain b-amyloid (Ab) levels in amyloid precursor protein transgenic mice, but no data are available on the effect that it may have on the other main pathologic features of AD such as tau. Methods 3xTg mice with diet-induced high Hcy were compared with mice having normal Hcy. Neuronal cells were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
112
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 31 publications
6
112
0
Order By: Relevance
“…The results from the Hcy-targeting intervention experiment strongly suggested that the stressinduced HHcy and subsequent up-regulation of Aβ could be one of the mechanisms of stress affecting the development of cognitive decline. A similar role for Hcy in Aβ pathogenesis has also been proved in transgenic AD mice with diet-induced HHcy (Li et al 2014) and in normal rats receiving daily Hcy injections (Chai et al 2013;Zhang et al 2009). These studies reported that Hcy could disturb the metabolism of Aβ and induce Aβ accumulation and cognition impairment both in AD or normal rodents.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The results from the Hcy-targeting intervention experiment strongly suggested that the stressinduced HHcy and subsequent up-regulation of Aβ could be one of the mechanisms of stress affecting the development of cognitive decline. A similar role for Hcy in Aβ pathogenesis has also been proved in transgenic AD mice with diet-induced HHcy (Li et al 2014) and in normal rats receiving daily Hcy injections (Chai et al 2013;Zhang et al 2009). These studies reported that Hcy could disturb the metabolism of Aβ and induce Aβ accumulation and cognition impairment both in AD or normal rodents.…”
Section: Discussionmentioning
confidence: 55%
“…Aβ1-40 and Aβ1-42 levels in hippocampal and cerebral extracts were assayed by sensitive sandwich ELISA kits (Wako Chemicals, Richmond, VA) according to the protocol described by the manufacturer (Li et al 2014).…”
Section: Elisa For Aβmentioning
confidence: 99%
“…Testing was always performed in the same room and at the same time to ensure environmental consistency as previously described (Di Meco et al ., 2014; Li et al ., 2014). Briefly, each mouse was placed in the center of the Y‐maze and allowed to explore freely during a 5‐min session as a measure of spontaneous alternating behavior.…”
Section: Methodsmentioning
confidence: 99%
“…To perform the Morris water maze (MWM), we used a white circular plastic tank (122 cm in diameter, walls 76 cm high), filled with water maintained at 22°±2°C, and made opaque by the addition of a nontoxic white paint, as previously described (Di Meco et al ., 2014; Li et al ., 2014). Mice were trained for four consecutive days to find a Plexiglas platform submerged in water from four different starting points.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation